Decision making in rural tourism management: the case of Algarve - Pego, Ana (2019)
Decision making is an important role performed by managers. This chapter will analyze the importance of information systems (IS) on the decision-making process at rural organizations in Portugal's Algarve region. Managers' perceptions were analyzed and compared with the decision-making process model proposed in this chapter, which was based on the models of Simon (1977) and Mintzberg, Raisinghani, and Theorêt (1976). This chapter will discuss the capacity of rural tourism organizations to solve problems, as well as review the time needed to solve problems through the use of IS. This chapter will conclude that IS in the organizational decision-making process is positively related to the identification of the decision-making problem and time needed to solve the problems. This investigation will allow other sectors the opportunity to discuss decision process models based on technology, information capability, and organizational competitiveness.